Dairy Nasal Lavage and Exposure Data - Erlandson, Grant (Colorado State University. Libraries, 2022)
Livestock workers experience an increased burden of bioaerosol-induced respiratory disease including high prevalence of rhinosinusitis. Dairy operations generate bioaerosols spanning the inhalable size fraction (0-100 μm) containing bacterial constituents such as endotoxin. Particles with an aerodynamic diameter between 10-100 μm are known to deposit in the nasopharyngeal region and likely affect the upper respiratory tract. We evaluated the effectiveness of a hypertonic saline nasal lavage in reducing inflammatory responses in dairy workers from a high-volume dairy operation. Inhalable personal breathing zone samples and pre-/post-shift nasal lavage samples from each participant over five consecutive days were collected. The treatment group (n=5) received hypertonic saline while the control group (n=5) received normotonic saline. Personal breathing zone samples were analyzed for particulate concentrations and endotoxin using gravimetric and enzymatic methods, respectively. Pro- and anti-inflammatory cytokines (i.e., IL-8, IL-10, and TNF-) were measured from nasal lavage samples using a multiplex assay. Inhalable dust concentrations ranged from 0.15 to 1.9 mg/m3. Concentrations of both pro- and anti-inflammatory cytokines, specifically IL-6, IL-8, and IL-10, were significantly higher in the treatment group compared to the control group (p < 0.02, p < 0.04, and p < 0.01 respectively). Further analysis of IL-10 anti-inflammatory indicates a positive association between hypertonic saline administration and IL-10 production. This pilot study demonstrates that hypertonic saline nasal lavages were successful in upregulating anti-inflammatory cytokines to support larger interventional studies.
Data set includes nasal pro and anti-inflammatory cytokine concentrations and dust and endotoxin exposure concentrations for dairy workers at a north Texas dairy taken in May of 2017.
Department of Environmental and Radiological Health Sciences